Effect of Plant Density and Soil Fertility on Pearl Millet Under Drought and Good Rainfall Situations - Garg, B K; Kathju, S; Vyas, S P; Lahiri, A N (Annals of Arid Zone, 2016)
Pearl millet (var. BJ 104) was grown in a drought and a good rainfall year with four plant densities (30,45,60 and 75 cm row providing about 2.17 X 10 516 to 0.91 x 10 5 plants ha--1) under low (20 kg ha--1 each of N and P2O5) and improved (80 kg ha-1 each of N and PzOs) soil fertility conditions. Crop performance, water use and nutrient uptake were better due to more favourable soil moisture conditions during the good, as compared to the drought year. However, ia both the years increased row spacing progressively increased the height, tiller number, leaf area,dzymatter, ' grain yield and N and P uptake plant-1. Water use increased with increased low spacing in a pod rainfall year but was unaffected by ptant population in the drought year. The improved performance of individual plants could possibly be attributed to larger milabilities of moisture and nutrients under wider row spacing. However, a decrease in plant population below a. 1.45 x l05 plants ha--1 or 45 cm row spacing reduced the dry matter production, grain yield, leaf and index, water use efficiency and uptake of N and P perunit of area in both theyears. It seems that irn performance of individual plants under wider spacing could not compensate for the logics accrued due to a decrease in plant population per unit area beyond a point. Improved soil fertility imparted significant beneficial effects, per plant or per unit area, in both the years. However, the magnitude of this effect was less in the drought year.